Relationship Analysis of Keyword and Chapter in Malay-Translated Tafseer of Al-Quran - Chua, S.; Nohuddin, P.N.E. (Universiti Teknikal Malaysia (UTEM), 2017)
A number of studies have gained popularity to study the unseen knowledge categories and relationship of subject matters discussed in the Al-Quran or the Tafseer. This research investigates the relationships between verses and chapters at the keyword level in a Malay translated Tafseer. A combination technique of text mining and network analysis is developed to discover non-trivial patterns and relationships of verses and chapters in the Tafseer. This is achieved through keyword extraction, keyword-chapter relationship discovery and keyword- chapter network analysis. A total of 130 keywords were extracted from six chapters in the Tafseer. The keywords and their relative importance to a chapter are computed using term weighting. A network analysis map was generated to visualize and analyze the relationship between keyword and chapter in the Tafseer. The relationship between the verses and chapters at the keyword level are successfully portrayed through the combination technique of text mining and network analysis. The novelty of this approach lies in the discovery of the relationships between verses and chapters that is useful for grouping related chapters together.